Investigation of Nucleation and Growth of Nanocrystalline Diamond Films Deposited at Low Temperature Using In Situ Laser Reflectance Interferometry. Issue 11 (28th August 2017) - Baudrillart, Benoit; Bénédic, Fabien; Tardieu, André; Achard, Jocelyn
Abstract : The nucleation and growth of nanocrystalline diamond (NCD) films deposited at low temperature on silicon substrates with a distributed antenna array (DAA) plasma enhanced chemical vapor deposition (PECVD) system is investigated using in situ laser reflectance interferometry (LRI). An optical model is developed using an effective media theory in order to describe the LRI signal recorded during NCD growth and to extract the nucleation density. The model is validated through comparisons with nuclei counting from Scanning Electron Microscopy (SEM) micrographs. LRI is then employed to investigate the influence of several ex situ pre‐treatments of silicon substrates. The nucleation density is estimated between 7.3 × 10 9 for ultrasonic abrasion with 40 μm diamond powder and 5.9 × 10 10 for seeding with 4.2 nm nanodiamond solution. The LRI technique is also employed to estimate in real time the critical thickness leading to the film delamination. The critical thickness for seeding methods is estimated in the range 485–545 nm, whereas no delamination is observed for the sample achieved on Si substrate pre‐treated by ultrasonic abrasion that reaches a thickness of 674 nm after a deposition of 20 h. Abstract : The nucleation and growth of nanocrystalline diamond films deposited at low surface temperature on silicon substrates with a distributed antenna array plasma enhanced chemical vapor deposition system is investigated using in situ laser reflectance interferometry. An optical model is developed in order to extract the nucleation density through reflectance measurements, as shown in the figure.